PENGARUH PENERAPAN ETIKA BISNIS ISLAM TERHADAP KINERJA PERUSAHAAN: STUDI ANALISIS PADA PT. SEMBAJA LAMPUNG - Deddy (Pojok Publisher, 2025)
This research is quantitative in nature, with the aim of providing measurable data that can be analyzed statistically, producing objective and generalizable findings. This research is also used to test hypotheses, identify causal relationships, and make predictions. In this study, qualitative data quantification was carried out, by converting descriptive data (not in the form of numbers) into quantitative data (in the form of numbers). The goal is to analyze qualitative data using statistical methods and other quantitative data analysis methods. In other words, qualitative data that was originally in the form of descriptions, narratives, or opinions, is converted into numerical form so that it can be calculated, measured, and then analyzed more systematically. This study concluded that the R Square value was 41.3%, which means that the variable of EBI implementation in the application of Islamic business ethics (X) influences company performance (Y) by 41.3%, while the remaining 58.7% is influenced by other variables not examined in this study. This study also recommends that further research add other factors that are estimated to affect company performance, such as motivation, compensation, and so on.